Samter’s Triad: pathogenesis, clinical picture, diagnosis, comparison of biological and surgical treatment and the role of aspirin desensitisation - Nowińska, Bianka; Piotrowski, Jan; Dorobisz, Karolina (Family Medicine & Primary Care Review, 2022)
Samter’s Triad (ST), also known as aspirin-exacerbated respiratory disease (AERD), is defined as the correlation of asthma, aspirin intolerance (AI) and nasal polyps (NP). The combination of these symptoms poses a challenge in clinical practice, i.e. difficulties in making diagnosis and managing treatment. The prevalence is estimated at 0.3–0.9% of the general population in the USA, with a slight female predominance, whereas among asthmatic patients, the prevalence is estimated at 10–11%. The most common symptoms of ST are nasal congestion, rhinorrhoea, sneezing, anosmia and sinus opacification with symptoms from the lower respiratory tract due to disease progression. Less common AERD manifestations are cutaneous and gastrointestinal symptoms. The diagnostics is based on a clinical picture, CT findings and provocative aspirin challenge. The treatment strategy is a combination of surgical treatment, aspirin desensitisation and biological treatment, such as Omalizumab or Dupilumab. Among the treatment options, the most beneficial strategy is aspirin desensitisation combined with FESS. The results of Omalizumab and Dupilumab treatment are promising, though they need to be confirmed by further studies. Our aim was to review the latest literature and compare the treatment options and their efficacy. We discussed pathogenesis, diagnosis, clinical picture, surgical and biological treatment options and aspirin desensitisation.